The Political Economy of Capital Income and Profit Taxation in a Small Open Economy. - Harry Huizinga; Søren Bo Nielsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 1997)
This paper considers the political economy of the mix of profit, investment and saving taxation in a small open economy where agents generally differ in their shares of profit and other income. In this setting, capital income taxation can have the dual role of financing government spending and of redistributing income. With majority voting, the paper can explain why distorting saving taxation exists, even if profits are not taxed to the fullest extent. Alternatively, saving may be subsidized, even if profit and investment are highly taxed. This paper further examines the role of the foreign ownership of domestic firms in explaining capital income taxation.
Keywords: 330